Predictors of early postoperative pain interference following orthopaedic surgery. - Kator, Jamie; Aneizi, Ali; Nadarajah, Vidushan; Sajak, Patrick M.J.; Zhan, Min; Gilotra, Mohit N.; Akabudike, Ngozi M.; Packer, Jonathan D.; Henn III, R. Frank (Journal of Orthopaedics, 2020)
Despite the increasing incidence of orthopaedic surgeries, there is a lack of data reporting on patient experience and recovery following surgery. As such, there is a need to better characterize the natural history of pain interference (PI) after orthopaedic surgery to better manage patients' expectations and recovery. To identify factors associated with greater pain interference two weeks following orthopaedic surgery. All patients undergoing elective outpatient orthopaedic surgery at a single urban academic institution were evaluated preoperatively from August 2016 to March 2018. Patients completed a baseline assessment consisting of demographic information, PROMIS computer adaptive testing in 6 domains including Pain Interference (PI), Physical Function, Social Satisfaction, Fatigue, Anxiety, and Depression. Two weeks following surgery, patients completed the same questionnaires along with assessments of Improvement and Satisfaction. Bivariate and multivariable regression analyses were performed. Categorical data was compared with ANOVA and continuous data was compared with Spearman's correlation coefficient (r s). 435 patients (age = 41.1 ± 15.7, 47% female) were studied. Mean PI was 60.1 ± 7.0 prior to surgery and 61.7 ± 7.6 at 2 weeks postoperative. Worse 2 week PROMIS PI was associated with lower extremity surgery, prior surgery on the joint, preoperative opioid use, depression, lower income, lower education, and higher ASA score (p < 0.05). Better 2 week PROMIS PI was correlated with better baseline and better 2 week scores on all outcome measures. Multivariable analysis demonstrated that lower extremity surgery, worse preoperative pain scores, and worse preoperative pain interference were independent predictors of worse pain interference after surgery. Early postoperative pain interference is associated with function, demographic, and psychosocial factors.